Ethanol and Isopropanol in Concentrations Present in Hand Sanitizers Sharply Reduce Excystation of Giardia and Entamoeba and Eliminate Oral Infectivity of Giardia Cysts in Gerbils - Chatterjee, Aparajita (Antimicrob Agents Chemother, 2015)
Enteric protozoan parasites, which are spread by the fecal-oral route, are important causes of diarrhea (Giardia duodenalis) and amebic dysentery (Entamoeba histolytica). Cyst walls of Giardia and Entamoeba have a single layer composed of fibrils of β-1,3-linked GalNAc and β-1,4-linked GlcNAc (chitin), respectively. The goal here was to determine whether hand sanitizers that contain ethanol or isopropanol as the active microbicide might reduce transmission of these parasites. We found that treatment with these alcohols with or without drying in a rotary evaporator (to model rapid evaporation of sanitizers on hands) kills 85 to 100% of cysts of G. duodenalis and 90 to 100% of cysts of Entamoeba invadens (a nonpathogenic model for E. histolytica), as shown by nuclear labeling with propidium iodide and failure to excyst in vitro. Alcohols with or without drying collapsed the cyst walls of Giardia but did not collapse the cyst walls of Entamoeba. To validate the in vitro results, we showed that treatment with alcohols eliminated oral infection of gerbils by 1,000 G. duodenalis cysts, while a commercial hand sanitizer (Purell) killed E. invadens cysts that were directly applied to the hands. These results suggest that expanded use of alcohol-based hand sanitizers might reduce the transmission of Giardia and Entamoeba.